Inferior Turbinate Size and CPAP Titration Based Treatment Pressures: No Association Found among Patients Who Have Not Had Nasal Surgery. (19th January 2016) - Camacho, Macario; Zaghi, Soroush; Tran, Daniel; Song, Sungjin A.; Chang, Edward T.; Certal, Victor
Abstract : Objective . To evaluate the effect of turbinate sizes on the titrated continuous positive airway pressure (CPAP) therapeutic treatment pressures for patients with obstructive sleep apnea (OSA) who have not had nasal surgery. Study Design . Retrospective case series. Methods . A chart review was performed for 250 consecutive patients. Results . 45 patients met inclusion criteria. The mean ± standard deviation (M ± SD) for age was54.6 ± 22.4 years and for body mass index was28.5 ± 5.9  kg/m 2 . The Spearman's rank correlation coefficient (r s ) between CPAP therapeutic treatment pressures and several variables were calculated and were weakly correlated (ager s = 0.29, nasal obstructionr s = - 0.30 ), moderately correlated (body mass indexr s = 0.42 and lowest oxygen saturationr s = - 0.47 ), or strongly correlated (apnea-hypopnea indexr s = 0.60 and oxygen desaturation index (r s = 0.62 )). No statistical significance was found with one-way analysis of variance (ANOVA) between CPAP therapeutic treatment pressures and inferior turbinate size (right turbinatesp value = 0.2012, left turbinatep value = 0.3064), nasal septal deviation (p value = 0.4979), or mask type (p value = 0.5136). Conclusion . In this study, CPAP titration based therapeutic treatment pressures were not found to be associated with inferior turbinate sizes; however, the CPAP therapeutic treatment pressures were strongly correlated with apnea-hypopnea index and oxygen desaturation index.